Lycopodiella cernua (L.) Pic. Serm.: an Extended Distributional Record for Northern Western Ghats of Maharashtra - Shaikh, Shakil D.; Patil, Anant P.; Dethe, U. L. (Indian Forester, 2018)
No Abstract.